Clinical Laboratory Profile of Blood Culture Proven Enteric Fever in Children - Shah, Subhash Chandra; Neupane, Prashank Shree; Guragain, Anusmriti; Dhakal, Ajaya Kumar (Journal of Nepal Paediatric Society, 2018)
Introduction: Enteric fever has diverse clinical presentations and laboratory findings and blood culture is gold standard for diagnosis in the children. This study was done to analyse clinical profile and laboratory findings in culture proven enteric fever. Material and Methods: The study was descriptive observational study carried out in the patient aged 14 years of age or less admitted with culture proven enteric fever admitted in a Paediatric ward of a tertiary medical centre in Lalitpur, Nepal from April 2009 to February 2018. Results: Forty children with blood culture proven were enrolled in the study. All children had fever with the mean duration of 5.3 days (1-14). The most common associated symptoms were gastrointestinal which included anorexia (47.5%), pain abdomen (37.5%), vomiting (37.5%), diarrhoea (15%) and constipation (5 %). Splenomegaly (25%) and hepatomegaly (17.5%) were the commonest signs. The majority of children (80%) had normal total leucocyte count and 32.5% of them had anaemia. There were no children with thrombocytopenia. Salmonella typhi and Salmonella paratyphi A were isolated in 70% and 30% of children respectively. None of the isolates showed drug resistance against ceftriaxone, chloramphenicol, cotrimoxazole, gentamicin, norfloxacin and ofloxacin. There was no mortality. Conclusions: Enteric fever should be suspected in all the children with fever for more than five days along with anorexia, gastrointestinal associated symptoms and normal white blood counts.